2021
DOI: 10.21037/atm-20-3095
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac indicator CK-MB might be a predictive marker for severity and organ failure development of acute pancreatitis

Abstract: Background: The prediction of severe acute pancreatitis (SAP) is the key to providing timely and targeted intensive care for acute pancreatitis (AP). The heart is one of multiple organs involved in the early stage of SAP, but the predictive ability of cardiac dysfunction for SAP remains elusive. We sought to determine if the serum levels of three cardiac indicators (CI) including N-terminal pro-brain natriuretic peptide (NT-proBNP), cardiac troponin I (cTNI), and creatine kinase myocardial band (CK-MB) at admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…Some studies proved that age increases with AP severity, 56 , 57 while other cohort studies reported no significant difference in age between non‐SAP and SAP, 58 , 59 , 60 which is also consistent with our current study and previous cohort study of 238 AP patients. 61 Furthermore, central obesity, hypertriglyceridemia (HTG), hypertension (HT), and diabetes mellitus (DM), a set of comorbidities termed metabolic syndrome (MetS), 62 were also reported ambiguous correlation with SAP. 59 , 63 Explanation for these paradoxical findings can be varied.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies proved that age increases with AP severity, 56 , 57 while other cohort studies reported no significant difference in age between non‐SAP and SAP, 58 , 59 , 60 which is also consistent with our current study and previous cohort study of 238 AP patients. 61 Furthermore, central obesity, hypertriglyceridemia (HTG), hypertension (HT), and diabetes mellitus (DM), a set of comorbidities termed metabolic syndrome (MetS), 62 were also reported ambiguous correlation with SAP. 59 , 63 Explanation for these paradoxical findings can be varied.…”
Section: Discussionmentioning
confidence: 99%
“…Their study also revealed the cardiac dysfunction can happen in the early stage of acute pancreatitis and is usually demonstrated by echocardiography (cardiac regional wall motion abnormalities and impaired diastolic function) and electrocardiography (T‐wave flattering and ST‐segment depression). 2 Although our patient had some nonspecific ST‐T change in ECG, echocardiography showed no systolic or diastolic dysfunction and no regional wall motion abnormality. Randeva et al 5 showed that the CK‐MB was less than 5% of total CK activity, and in myocardial involvement increased over time that peaks 24 h later, while in extracardiac elevation of MB isoenzyme a plateau pattern may be more common.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, myocardial injury unlikely caused the elevation of the CK/CK‐MB. On the contrary, Zao et al 2 . reported elevated CK activity that may rarely occur in patients with acute pancreatitis peaked 1 day after admission.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations